Incipient motion of surf zone sediments. Issue 8 (16th August 2015) - Frank, Donya; Foster, Diane; Sou, In Mei; Calantoni, Joseph
Abstract Incipient motion experiments were conducted with natural gravel, acetate beads, and coarse‐gravel‐sized electronic grains called Smart Sediment Grains in a Small‐Oscillatory Flow Tunnel. Measurements of fluid velocity were made using Particle Image Velocimetry. The strength of the fluid shear stresses and the pressure gradients were examined for a range of oscillatory flow conditions at the onset of motion of the sediment particles to determine which mechanism had induced particle motion. The three sediment types utilized in these experiments facilitated an assessment of the effects of sediment grain size diameter, shape, and density on incipient motion. Results suggested that the onset of sediment motion was dominated by the pressure gradients for flows with small orbital excursion amplitudes, by the shear stresses for flows with large orbital excursion amplitudes and by the combined effects for intermediate flows. The denser, angular gravel required greater free‐stream accelerations to trigger sediment motion than the spherical, less dense acetate beads, and Smart Sediment Grains. A combined parameter for incipient motion that accounts for the simultaneous effects of both shear stresses and pressure gradients while depending on the static coefficient of friction and the packing concentration of the mobile bed layer was evaluated for accuracy using a range of sediment types. The results suggested that the combined parameter may be a better indicator of sediment mobilization under oscillatory flows than the typically assumed shear stress criterion.